Percepção do graduando de enfermagem sobre sua saúde mental no estágio curricular - Nascimento, Márcia Gabriela Gomes (2018)
The present work aimed to understand how the nursing student perceives his mental health in the process of professional training during the Compulsory Curricular Internship. We adopted the methodology of a qualitative approach anchored in Phenomenology and in the existentialist methodological theoretical framework in the light of the philosopher Heidegger. The study participants were undergraduate nursing students who attended the Mandatory Curricular Internship. Data collection was performed in the second half of 2016, using the focal group technique used in the guiding question: Speak about the nursing academic being in the curricular stage in relation to their mental health. The project was approved by the Committee of Ethics in Research under the Opinion: 1,725,400, CAAE: 58451516.0.0000.5142. The data were analyzed using the three moments of phenomenology which are: description, reduction and understanding. The results showed 3 categories and 9 subcategories, which are: "the nursing academic: experiences and confrontation" that emerged three subcategories: feelings experienced during the curricular stage; experiences and difficulties in the curricular stage and experiences of the nursing academic: consequences and strategies. The second category "the nursing academic and the relationship with the other", and in this emerged three subcategories: the nursing student in search of support; the nursing student in the relationship with the teacher and the team and, finally, the nursing student experiencing collections in their daily lives. Finally, the third category was "the nursing academic and the world of curricular traineeship", and it comprised three subcategories: experiences of the differences between the areas; the positive points in relation to the curricular stage and the uncertainties of tomorrow in the nursing profession. It is considered that the nursing academic when inserted in his world of practice he / she passes through existential questions that involve the being-there while existing, becoming an entity in a world of everyday situations that require of him to live with different others, which are made to reflect in a dialectic between being, being, dasein demanding of the academic being to confront itself and the world in which it is launched. This, it has shown as a factor that alters the mental health of the same and is seen by him as suffering. It is pertinent that higher education institutions develop policies and strategies that can help the future student not only in aspects of the profession but also in aspects of personal existence enabling them to have less experienced experiences.